THE EVOLUTION OF EDUCATIONAL SERVICE MARKETING AND RELATIONAL MARKETING IN ISLAMIC OF EDUCATION INSTITUTIONS - Zohriah, Anis; Firdaus, Arif Fakih; Idris, Ahmad; Nuroniyah, Mila; Muin, Abdul (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2026)
Service marketing in the education sector is now focused on experiences, service quality, and long-term relationships with students and parents. Relational marketing is becoming increasingly important to create loyalty, involving technologies such as social media and student management systems. This research analyzes the evolution of marketing strategies and the challenges in building sustainable relationships. The research method is qualitative through a literature review. Data collection is done through documentation techniques. Data processing includes reduction, content analysis, data presentation, and data generalization. The results of the study indicate: Educational service marketing aims to introduce services to prospective students and parents, while increasing awareness, interest, and trust. Its strategies include promoting the institution's image, educational excellence, facilities, and learning experiences. In the digital age, technology and social media are used to build brand awareness and offer relevant and flexible educational programs. Relational marketing focuses on building long-term relationships with students, parents, alumni, and the community. Flexible, personalized services, along with the empowerment of technology, improve retention, loyalty, and positive recommendations. Engaged alumni strengthen the institution's reputation and expand its network. Key strategies include digital marketing, data-driven marketing, and customer experience.